Reducing the water stress inflicted by Sweden’s food consumption on other countries through sustainable food options - Study focusing on the water stress Sweden inflicts due to coffee and meat import - Nika, Drini; Chamoun, Elias (My University, 2024)
This study delves into strategies for Sweden to curtail food imports from water-stressed nations and advance sustainable food production. Initially, we calculate the water footprint of meat and coffee consumption in Sweden, evaluating its impact on both Sweden and its importing countries. The main findings reveal that while Sweden's water stress in 2020 was 3.58%, transitioning to 100% environmentally friendly options, such as producing alternatives to imported coffee and meat within Sweden, resulted in a 0.0214% increase in the country's water stress, thereby increasing Sweden's water stress by a small margin. This would, however, significantly decrease the water stress for other countries which Sweden imports from. The study then explores solutions, emphasizing increased domestic production, water-efficient practices, and consumer awareness. Shifting from meat to plant-based alternatives and opting for sustainable coffee substitutes reduces Sweden's water footprint. The conclusion underscores the significance of transitioning to environmentally friendly options like plant-based meat and chicory plants to foster a resilient and sustainable food system in Sweden while minimizing water stress on other nations.
Keywords: Water scarcity; water stress; water consumption pattern; total freshwater withdrawn; water footprint; environmental options